Years of potential life lost due to HIV-AIDS infection and associated factors in Yogyakarta - Ana Nurjanah Andarwatolanrain; Bambang Riyanto; Hari Kusnanto (Berita Kedokteran Masyarakat (BKM), 2016)
PurposeThe purpose of this paper was to describe the number of Years of Potential Life Lost due to HIV-AIDS infection and the factors affecting. MethodA retrospective cohort study was conducted using medical record data for all patients diagnosed with HIV-AIDS and has died in Dr. Sardjito Yogyakarta, related to sociodemographic characteristics, behavior and clinical conditions at diagnosis. The cut-off point used to calculate Years Potential Life Lost  is 65 years.ResultsThe study found that first, 193 deaths occurred during 2010 to 2015. Second, most of the HIV-AIDS patients who died were men (71%), married (47%), infected through heterosexual (27%), never followed ARV therapy (73%), had moderate anemia (37%) and was in 3rd stage (50%). Third, the Years of Potential Life Lost average is 31.12 years. Fourth, female gender, unmarried and suffer from anemia are factors that affect the number of Years Potential Life Lost cases in HIV / AIDS patients.ConclusionThe average Years of Potential Life Lost in HIV-AIDS patients in Yogyakarta is quite high. HIV-AIDS patients diagnosed at a younger age (<50 years), female, unmarried and suffered from severe anemia had more Years of Potential Life Lost than patients diagnosed at age ≥ 50 years, male, married or divorced and not suffered from anemia.  Intensive HIV screening by the DIY Health Office and hospitals, as well as comprehensive education on HIV and AIDS for both at-risk groups and the general public, can raise awareness of HIV sufferers for antiretroviral therapy before they are in severe clinical and consequent conditions at an early death.